2014
DOI: 10.1002/adma.201403509
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Electrospun Nanofiber Matrices Via Localized Dissolution: Potential for Guided Tissue Formation

Abstract: With the assistance of an ink-jet printer, solvent (the "ink") can be controllably and reproducibly printed onto electrospun nanofiber meshes (the "paper") to generate various micropatterns and subsequently guide distinct cellular organization and phenotype expression. In combination with the nanofiber-assisted layer-by-layer cell assembly, the patterned electrospun meshes will define an instructive microenvironment for guided tissue formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…The first one relies on the precise manipulation of the electrospinning process via either introducing collectors with micro/nanoscale layouts, incorporating magnetic nanoparticles into the fiber matrix and simultaneously imposing a magnetic field, or employing near‐field electrospinning . Instead of direct control over electrospinning, the second one realizes the microstructures through post‐modification of electrospun nanofibers using typical microelectromechanical system or inject‐printing . Despite the remarkable flexibility in microstructures induced by lithography, the state‐of‐the‐art technology is limited both by the possible contamination from residual photoresists and by the applicable materials (photocurable materials).…”
Section: Methodsmentioning
confidence: 99%
“…The first one relies on the precise manipulation of the electrospinning process via either introducing collectors with micro/nanoscale layouts, incorporating magnetic nanoparticles into the fiber matrix and simultaneously imposing a magnetic field, or employing near‐field electrospinning . Instead of direct control over electrospinning, the second one realizes the microstructures through post‐modification of electrospun nanofibers using typical microelectromechanical system or inject‐printing . Despite the remarkable flexibility in microstructures induced by lithography, the state‐of‐the‐art technology is limited both by the possible contamination from residual photoresists and by the applicable materials (photocurable materials).…”
Section: Methodsmentioning
confidence: 99%
“…In the course of fiber collection, it is possible to manipulate the distribution of electric fields for achieving unique spatial organization of fibers to accommodate the anisotropy of native ECM, for example, fibers collected on a rotatory mandrel exhibit an orientation parallel to the rotating direction . In addition, intervention of electric field distribution by using a patterned collection surface can correspondently affect fiber deposition to introduce unique fiber organization within electrospun mats . Studies have shown that such patterned fiber mats can yield better mechanical strength and induce distinctive cellular responses on their surface .…”
Section: Introductionmentioning
confidence: 99%
“…31 In addition, intervention of electric field distribution by using a patterned collection surface can correspondently affect fiber deposition to introduce unique fiber organization within electrospun mats. [32][33][34] Studies have shown that such patterned fiber mats can yield better mechanical strength and induce distinctive cellular responses on their surface. 35,36 However, it is unclear whether such electrical field-induced modulation of fiber organization can effectively increase the interfiber distance for cell infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…The 2D structure and the small pore size (≈2 μm) hinder cells to migrate into the interior of the fibers, thus limiting the space for cell growth as well as the overall morphologies . Moreover, they cannot effectively provide an ECM‐like microenvironment for cell growth, which causes a number of limitations for their practical applications in tissue engineering fields . Thus, it is highly desired to develop 3D aligned fibers which can provide topographical cues to induce and enhance cellular growth.…”
Section: Introductionmentioning
confidence: 99%